2008
DOI: 10.1016/j.compscitech.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of delamination position in cross-ply laminated composite beams using S0 Lamb mode

Abstract: In this work, a Lamb wave based technique has been developed for delamination detection in cross-ply laminated beams. By measuring the propagation speed of S 0 Lamb mode and the traveling time of a signal reflected from a delamination site, the location of the delamination can be identified. It has been also confirmed by the experiment that the location of a delamination can be accurately determined by only using the data collected from the sensors in a defect-containing beam, without referring to the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 10 publications
(19 reference statements)
0
44
0
Order By: Relevance
“…This wave mechanism is called mode conversion and it also occurs when the wave reaches the edge of a plate, so new wave modes are created and reflected backwards. Mode conversion in delaminations has been studied in several investigations in order to take advantage of these changes and use them to detect and locate these defects (Su et al 2007;Hu et al 2008;Ramadas et al 2009). Hu et al (2008) analysed numerically the propagation of the S 0 mode through a delamination.…”
Section: Damage Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This wave mechanism is called mode conversion and it also occurs when the wave reaches the edge of a plate, so new wave modes are created and reflected backwards. Mode conversion in delaminations has been studied in several investigations in order to take advantage of these changes and use them to detect and locate these defects (Su et al 2007;Hu et al 2008;Ramadas et al 2009). Hu et al (2008) analysed numerically the propagation of the S 0 mode through a delamination.…”
Section: Damage Detectionmentioning
confidence: 99%
“…Mode conversion in delaminations has been studied in several investigations in order to take advantage of these changes and use them to detect and locate these defects (Su et al 2007;Hu et al 2008;Ramadas et al 2009). Hu et al (2008) analysed numerically the propagation of the S 0 mode through a delamination. When the S 0 mode enters in the delamination, a small amount of the energy of S 0 (almost undetectable) is reflected backwards and most of it is transmitted forward, but also mode conversion is produced, so a new A 0 mode is reflected and a new A 0 mode is transmitted.…”
Section: Damage Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various non-destructive testing (NDT) methods, such as electrical, X-ray imaging and tomography, thermography, acoustic emission and ultrasonic inspection, have therefore been developed for the detection of defects in CFRP materials, components and structures [1][2][3][4][5][6][7][8][9][10]. Of these, ultrasonic NDT is probably the most widespread, with linear ultrasonic C-scan imaging and Lamb-wave measurement techniques being the most well-known [8,[11][12][13][14]. These well-established linear acoustic methods rely on the measurement of the reverberation, reflection, scattering, transmission or absorption of acoustic energy.…”
Section: Introductionmentioning
confidence: 99%
“…The triangulation technique by several sensors was developed according to the difference in arrival times of A 0 mode wave from the vibration source [2]. With S 0 mode, Hu et al identified the delamination position in cross-ply laminated composite beams [3].…”
Section: Introductionmentioning
confidence: 99%